Information model operation and maintenance data network security construction based on partitioned blockchain - Chen, Fuyang; Yao, Jie; Xu, Zihan (Frontiers in Blockchain, 2025)
In response to the problems of single point of failure risk and poor scalability in current network security construction, this article applies an information model operation and maintenance data network security construction method based on partitioned blockchain. The effectiveness and advantages of the partitioned blockchain method used is evaluated in a comparison with traditional models. The research results show that the overall recall rate of the adopted method for daily network attacks is very high. Compared with traditional models, the CPU and memory usage are lower, ensuring the scalability and efficiency of blockchain while achieving a more reliable information operation and maintenance.